ANALISIS KEPUASAN KONSUMEN DI CAFÉ ONE REFINERY KOTA PEKANBARU - Utomo Ramadhan Ivan; Wasnury Rendra; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research has the aim of determine the consumer satisfaction index andstrategies to improve the service quality of Café One Refinery Pekanbaru City.The population in this study includes all visitors to Café One Refinery PekanbaruCity, totaling 100 people. The sample was determined using purposive samplingmethod. In this study, the sample studied used a questionnaire. Hypothesis testingin this study uses CSI (Customers Satisfaction Index) analysis and IPA(Importance Performance Analysis) analysis with the help of the SPSS program.The results showed that the overall consumer satisfaction index given by CaféOne Refinery Pekanbaru City was "Very Satisfied" based on the results ofcalculations from the CSI method with a value of 85.91%. Based on the results ofthe calculation of the IPA method with a value of 97.77%. Then, the strategy toimprove the service quality of Café One Refinery Pekanbaru City is prioritized on3 indicators as follows: Locations that are easy to find (IPA-Indicator 1); Easyaccess to parking lots (IPA-Indicator 2); Presentation of orders in accordancewith the time promised (IPA- Indicator 18). Keywords: customers satisfaction, customers satisfaction index (csi), importanceperformance index (ipa)